2014
DOI: 10.4236/ojn.2014.46047
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Mean Number of Consonant-Vowel-Consonant Words Decoded between Letter-Sound Readers and Non Letter-Sound Readers

Abstract: Children's failure to develop simple word decoding skills in early years is linked to future poor reading, school dropout, and poor health [1] [2]. Letter-sound knowledge is needed for word decoding development; however questions remain on what types of letter-sound knowledge help children decode simple words [3]. This study investigated the differences in mean number of consonant-vowel-consonant (CVC) words decoded between two groups of children, a letter-sound reading group and non letter-sound reading group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 70 publications
(209 reference statements)
1
12
0
Order By: Relevance
“…Interesting too was the finding that many children from both the intervention group and control group could name letters yet could not decode CVC words unless letter-sound reading was a skill. These results are consistent with earlier research showing children who could letter-sound read were the better CVC word decoders (Wolf 2014). The results are also consistent with a multitude of prior research showing children who received letter name instruction alone did not improve in reading ability (Adams 1990).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Interesting too was the finding that many children from both the intervention group and control group could name letters yet could not decode CVC words unless letter-sound reading was a skill. These results are consistent with earlier research showing children who could letter-sound read were the better CVC word decoders (Wolf 2014). The results are also consistent with a multitude of prior research showing children who received letter name instruction alone did not improve in reading ability (Adams 1990).…”
Section: Discussionsupporting
confidence: 93%
“…To attain automatic decoding skills, the print-to-sound processing must be practiced (NIFL 2008). This study builds on a previous quantitative descriptive study which showed children who could letter-sound read were the better CVC word decoders when compared to children who had low or no letter-sound reading abilities (Wolf 2014). The next step in reading research was to begin to determine what types of teaching strategies foster letter-sound reading.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…When children are first learning to read, the speed of oral reading is individualized (Wolf, 1998;2014). Veenendaal et al (2015) note when children are learning to read, the reading is not fluent.…”
Section: Case Scenariomentioning
confidence: 99%